Is training and development imperative? A bibliometric and systematic literature review - Binmlafikh, Mohammed Abdulmohsen; Wahab, Shah Rollah Bin Abdul (Edelweiss Applied Science and Technology, 2025)
Training and development play a significant role in improving employee skills and capabilities for higher performance and in producing high-quality work. They are important for ensuring employee efficiency and for organizations to cultivate a professional workforce. The aim of this bibliometric and systematic literature review is to address the research gap and serve as a guideline for policymakers, academicians, and organizations in effectively utilizing training and development. The current study followed the Preferred Reporting Items for Meta-Analyses (PRISMA) and Systematic Reviews. The Scopus database was used due to its broad journal coverage. A holistic keyword search identified 2,299 articles, and after applying criteria, 169 relevant articles were gathered. Quantitative methods were commonly used, followed by qualitative and mixed methods. Descriptive statistics, Structural Equation Modeling (SEM), exploratory factor analysis, and multiple regression were common statistical techniques. This review enriched the literature and suggested future directions for understanding training and development and refining methodological approaches. The study recommends customized methods, innovative technologies, and the integration of AI in training frameworks.